2002
DOI: 10.1109/68.980530
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a four-channel WDM/OCDMA system using 255-chip 320-Gchip/s quarternary phase coding gratings

Abstract: Abstract-In this letter, we report the fabrication and application of 255-chip 320 Gchip/s quaternary phase superstructure fiber Bragg gratings (SSFBGs) for optical code generation and recognition in a four-channel wavelength-division-multiplexing (WDM)/optical code-division-multiplexing (OCDM) experiment. Individual users of the system operate with different coding schemes, repetition rates, and wavelengths. Our experiments show that a single SSFBG can be used to perform simultaneous optical decoding and wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 6 publications
0
31
0
1
Order By: Relevance
“…The amount of timing jitter that can be compensated for is determined by the width of the rectangular pulses and can be readily adjusted to fit the specific jitter characteristic of a given transmission system. It has already been demonstrated that SSFBG technology is suitable for generating temporal features as short as 3.1 ps [11], a number that by no means represents the ultimate limit of the technology. The combination of rectangular pulses with such a short pulse width with nonlinear optical switches that exploit the ultrafast Kerr effect in optical fibers (femtosecond response times) should allow the regeneration of signals with bit rates as high as 320 Gb/s.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of timing jitter that can be compensated for is determined by the width of the rectangular pulses and can be readily adjusted to fit the specific jitter characteristic of a given transmission system. It has already been demonstrated that SSFBG technology is suitable for generating temporal features as short as 3.1 ps [11], a number that by no means represents the ultimate limit of the technology. The combination of rectangular pulses with such a short pulse width with nonlinear optical switches that exploit the ultrafast Kerr effect in optical fibers (femtosecond response times) should allow the regeneration of signals with bit rates as high as 320 Gb/s.…”
Section: Discussionmentioning
confidence: 99%
“…A discrete phase shift is typically achieved by shifting the phase of the rapidly varying refractive index during the grating inscription process. This has been successfully exploited for phase encoding of data signals in OCDMA systems [2]. On the other hand, a confined chirp will also produce similar effect as a result of the change in the local propagation constant.…”
Section: Device Principle and Descriptionmentioning
confidence: 99%
“…OCDMA systems have advanced to a stage where 255-chip systems have been experimentally demonstrated, utilizing superstructured fiber Bragg grating (SSFBG) technology [2]. Nevertheless, definite advancement of the optical transmission systems to dynamically reconfigurable networks brings about the need for this multiplexing system to include tuning capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…One main advantage of the CDS-OCDMA technique is that it can be exploited in combination with WDM signals or conveyed into WDM bands as has been previously proposed by several authors [2,7,8]. In [2] a Coarse WDM/OCDMA system is proposed employing codes with 511 chips and 10 nm width-channel, this approach implies 5 nm channel separation and thus is hardly applicable with 100 GHz WDM separation.…”
Section: Introductionmentioning
confidence: 99%
“…OCDMA is an emergent technology limited until now for the immaturity of optical devices, however recently a great progress has been observed in the en/decoder devices and time gating techniques [3] that makes OCDMA a good alternative for multiple access solution in FTTH implementations. In particular, the Coherent Direct Sequence (CDS) OCDMA technique has been demonstrated employing different technologies as en/decoder devices such as planar lightwave circuits and superstructured fiber Bragg gratings (SSFBG) and applied for multiple user access networks [4][5][6][7]. Standard single channel CDS technique consists in: 1) one optical pulse is applied to the encoder which must provide N copies of it, called chips, along the time axis separated by the inter-chip time tch.…”
Section: Introductionmentioning
confidence: 99%